65.3k views
2 votes
Let f(x) = 3 − x . Find the average rate of change of f(x) from x = a to x = a + h and simplify your answer so that no single factor of h is left in the denominator.

2 Answers

0 votes

Answer: on usatestprep the answer is c.

Explanation:


(-1)/(√(a) +√(a+h) )

User ANAS AJI MUHAMMED
by
5.0k points
3 votes

Answer:

The average rate of change of f(x) from x = a to x = a + h is -1

Explanation:

Average rate of the function f(x) over [a, b] is given by:


A(x) = (f(b)-f(a))/(b-a)

Given the function:


f(x) = 3-x

At x=a

f(a) = 3-a

At x = a+h

then;

f(a+h) = 3-(a+h) = 3-a-h

Using the formula for average rate of function:


A(x) = (f(x+h)-f(x))/(x+h-x)

Substitute the given values we have;


A(x) = (3-a-h-(3-a))/(x+h-x)

Simplify:


A(x) = (3-a-h-3+a)/(h)

or


A(x) = (-h)/(h) = -1

Therefore, the average rate of change of f(x) from x = a to x = a + h is, -1

User Racheli
by
4.7k points